IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM DIMENSI BERNALAR KRITIS MELALUI PROYEK PADA KURIKULUM MERDEKA - Insani, Zulaiha Nurul; Azani, Mohammad Zakki; Mustofa, Triono Ali (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study investigates in depth the implementation of Islamic Religious Education (PAI) learning that is oriented towards developing students' critical reasoning dimensions through the implementation of projects within the Merdeka Curriculum framework. This qualitative case study focuses on two junior high school educational institutions, namely SMP Negeri 1 Teras and SMP Negeri 2 Teras, with the main objective of exploring how students can successfully face future educational challenges by honing their critical reasoning skills. Achieving this educational idealism requires close synergy and cooperation between teachers as facilitators, parents as supporters in the home environment, and students as active subjects of learning. In the context of PAI, fundamental values ??such as monotheism, aqidah, and morals are the main foundations integrated into learning to encourage students to reason critically without neglecting the essence of religious teachings. A qualitative approach through the case study method was chosen to understand how these values ??can be applied in real terms in students' daily lives, both in the school environment and in their social interactions. Data collection was carried out comprehensively through participatory observation, in-depth interviews, and analysis of related documentation. To ensure the validity of the data, triangulation techniques of methods and sources were applied, followed by data analysis which included data reduction stages, systematic data presentation, and drawing conclusions. The results of the study indicate that efforts to highlight students' critical reasoning skills through projects in Islamic Religious Education learning are highly dependent on the pedagogical and substantive readiness of teachers, the availability of adequate support for facilities and infrastructure, constructive cooperation with parents, and a commitment to ensure that project implementation does not deviate from the essence of religious values. ABSTRAKPenelitian ini secara mendalam menginvestigasi implementasi pembelajaran Pendidikan Agama Islam (PAI) yang berorientasi pada pengembangan dimensi bernalar kritis siswa melalui penerapan proyek dalam kerangka Kurikulum Merdeka. Studi kasus kualitatif ini difokuskan pada dua institusi pendidikan menengah pertama, yaitu SMP Negeri 1 Teras dan SMP Negeri 2 Teras, dengan tujuan utama untuk mengeksplorasi bagaimana siswa dapat berhasil menghadapi tantangan pendidikan di masa mendatang dengan mengasah kemampuan bernalar kritis mereka. Pencapaian idealisme pendidikan ini memerlukan sinergi dan kerjasama yang erat antara guru sebagai fasilitator, orang tua sebagai pendukung di lingkungan rumah, dan siswa sebagai subjek aktif pembelajaran. Dalam konteks PAI, nilai-nilai fundamental seperti tauhid, akidah, dan akhlak menjadi landasan utama yang diintegrasikan ke dalam pembelajaran untuk mendorong siswa bernalar kritis tanpa mengesampingkan esensi ajaran agama. Pendekatan kualitatif melalui metode studi kasus dipilih untuk memahami bagaimana nilai-nilai tersebut dapat diaplikasikan secara nyata dalam kehidupan sehari-hari siswa, baik di lingkungan sekolah maupun dalam interaksi sosial mereka. Pengumpulan data dilakukan secara komprehensif melalui observasi partisipatif, wawancara mendalam, dan analisis dokumentasi terkait. Untuk menjamin keabsahan data, teknik triangulasi metode dan sumber diterapkan, diikuti dengan analisis data yang meliputi tahap reduksi data, penyajian data secara sistematis, dan penarikan kesimpulan. Hasil penelitian mengindikasikan bahwa upaya menonjolkan kemampuan bernalar kritis siswa melalui proyek dalam pembelajaran PAI sangat bergantung pada kesiapan guru secara pedagogis dan substantif, ketersediaan dukungan sarana dan prasarana yang memadai, kerjasama konstruktif dengan orang tua, serta komitmen untuk tetap menjaga agar implementasi proyek tidak menyimpang dari esensi nilai-nilai keagamaan.